Completion and determinants of a continuum of care in maternal health services in Benishangul Gumuz region: A prospective follow-up study - Zelka, Muluwas Amentie; Yalew, Alemayehu Worku; Debelew, Gurmesa Tura (Frontiers in Public Health, 2022)
Introduction: Provision of a continuum of care (COC) to women throughout pregnancy, labour, and delivery has become a fundamental program strategy for improving maternal and neonatal health. A better understanding of where the gaps are in seeking care along the pathway and what factors contribute to the gaps is required for successful program implementation. Hence, this study was targeted to determine the status of continuum of care and determinant factors that influence the completion rate of continuum of care in maternal health services. Methods: A prospective follow-up study was conducted among 2,198 sampled pregnant women and followed for 11 months in Benishangul Gumuz Region. A multistage clustered sampling technique was employed to select the study participants. Data were collected via face-to-face interviews using a pretested, semi-structured, logbook registry, and interviewer questionnaire. Collected data were edited, cleaned, and analyzed using STATA software. Multilevel model was used to examine the effects of individual and community-level factors on the completion of the continuum of care and expressed as AOR with 95%CI. Results: The completion rate of a continuum of care via visit-based, content-based, and space dimensions were 33.1%, 20%, and 37.2%, respectively. The enabling factors were having information on maternal health services (AOR=2.25;95%CI:1.11-4.55), iron-folic acid supplementation (AOR=2.58;95%CI:1.37-4.86), tetanus toxoid vaccination during pregnancy (AOR=2.21;95%CI:1.39-3.52), have pregnant related problems (AOR=2.1;95%CI:1.15-3.71), dry and stimulate newborn (AOR=2.61;95%CI:1.42-4.77), appropriate cord care(AOR=2.01;95%CI:1.07-3.79) and immunizing newborn (AOR=6.9;95%CI:3.79-12.59). Whereas, risk factors were ever having a stillbirth (AOR=0.52;95%CI:0.32-0.85) and delay of 1st ANC initiation at 4–6 months (AOR=0.45;95%CI:0.3-0.68). Conclusion: Completion rates via visit-based, content-based, and space dimensions were low. Different determinant factors were identified, which have a programmatically important implication. Thus, interventions should focus on increasing women’s awareness and improving the availability of whole packages of maternal health services at nearby health facilities to facilitate the completion rate.